PENGARUH GAYA KEPEMIMPINAN, BUDAYA ORGANISASI DAN KOMITMEN TERHADAP KINERJA PEGAWAI PADA KANTOR SEKRETARIAT DEWAN PROVINSI (DPRD) PAPUA BARAT DAYA - Pelipus Wamban; Pahmi Pahmi; Andi Irwan (JURNAL LENTERA BISNIS, 2026)
This study aims to determine and analyze the influence of leadership style, organizational culture, and commitment on employee performance at the Secretariat Office of the Regional People's Representative Council (DPRD) of Southwest Papua Province. The type of research used is descriptive quantitative with a quantitative approach. The population in this study was all employees of the Secretariat Office of DPRD Southwest Papua Province, totaling 80 people. The sampling technique used saturated sampling, where the entire population was sampled. Data collection method used a questionnaire with a Likert scale that had been tested for validity using Pearson Product Moment correlation and reliability using the Alpha Cronbach method. The data analysis technique used was multiple linear regression analysis. The results showed that partially, leadership style had a positive and significant effect on employee performance with a significance value of 0.000 and t-count of 4.642. Organizational culture had no significant effect on employee performance with a significance value of 0.152 and t-count of -1.446. Organizational commitment had a positive and significant effect on employee performance with a significance value of 0.008 and t-count of 2.723. Simultaneously, leadership style, organizational culture, and organizational commitment had a significant effect on employee performance with an F-count of 65.609 and a significance of 0.000. The coefficient of determination (R Square) was 0.721, meaning that 72.1 percent of the variation in employee performance could be explained by these three independent variables, while the remaining 27.9 percent was explained by other variables outside this study. The conclusion of this study is that leadership style and organizational commitment are proven to be important factors that can improve employee performance, while organizational culture has not yet had a significant influence in the context of the Secretariat Office of DPRD Southwest Papua Province. Suggestions for office leaders are to maintain and improve effective leadership styles, seriously revitalize organizational culture, and maintain and strengthen employee commitment through attention to welfare, career development, and the creation of a conducive work environment.